The Maker of History: Pemimpin yang Berwawasan Oikumenis di Indonesia - Eibenhaizer I.N Timo (PAX HUMANA, 2015)
Leader is one of the most important key in moving the organizations life and promote life together. However the role of leaders is only 20% compared to the followers in the dynamics of the organization, but leaders become role models and inspiration ?igures. This article discusses about the role of leader in the context of the ecumenical movement. The author tries to extend the understanding of the ecumenical movement is not just an efforts towards the uni?ication of Christians, but to the understanding of the early ecumenical, the inhabited world, which refers to how the leader of the Christian being a role model and inspiration in an effort to bring together the various components of the community who inhabit the earth for unite to build the world. Some Christian leaders in Indonesia who are leaders in many ?ields, the author adopted as a spotlight in this discussion. They include: Oerip Notohamidjojo for education, WS Renda in the ?ield of art, and Basuki Tjahaja Purnama in the arena of politics and government. Keywords: Leader, Ecumenical Movement, Churches in Indonesia